Annotated Bibliography Perpustakaan Tun Abdul Razak Issue 2/2021 - Jabatan Perancangan dan Pembangunan Perpustakaan, Bahagian Sumber Bercetak (Perpustakaan Tun Abdul Razak, 2021)
The Annotated Bibliography Perpustakaan Tun Abdul Razak, Universiti Teknologi MARA is a reading list or bibliography to elucidate, evaluate or describe the subject and contents of a book. The listed bibliography is a collection of Perpustakaan Tun Abdul Razak in Shah Alam Campus and all other campuses in UiTM. It will be published quarterly (4 issues a year).